Multiple spinal nerve enlargement and SOS1 mutation: Further evidence of overlap between neurofibromatosis type 1 and Noonan phenotype. Issue 1 (15th September 2017) - Santoro, C.; Giugliano, T.; Melone, M.A.B.; Cirillo, M.; Schettino, C.; Bernardo, P.; Cirillo, G.; Perrotta, S.; Piluso, G.
Abstract : Neurofibromatosis type 1 (NF1) has long been considered a well‐defined, recognizable monogenic disorder, with neurofibromas constituting a pathognomonic sign. This dogma has been challenged by recent descriptions of patients with enlarged nerves or paraspinal tumors, suggesting that neurogenic tumors and hypertrophic neuropathy may be a complication of Noonan syndrome with multiple lentigines (NSML) or RASopathy phenotype. We describe a 15‐year‐old boy, whose mother previously received clinical diagnosis of NF1 due to presence of bilateral cervical and lumbar spinal lesions resembling plexiform neurofibromas and features suggestive of NS. NF1 molecular analysis was negative in the mother. The boy presented with Noonan features, multiple lentigines and pectus excavatum. Next‐generation sequencing analysis of all RASopathy genes identified p.Ser548Arg missense mutation in SOS1 in the boy, confirmed in his mother. Brain and spinal magnetic resonance imaging scans were negative in the boy. No heart involvement or deafness was observed in proband or mother. This is the first report of a SOS1 mutation associated with hypertrophic neuropathy resembling plexiform neurofibromas, a rare complication in Noonan phenotypes with mutations in RASopathy genes. Our results highlight the overlap between RASopathies, suggesting that NF1 diagnostic criteria need rethinking. Genetic analysis of RASopathy genes should be considered when diagnosis is uncertain. Abstract : Bilateral cervical and lumbar spinal lesions compatible with neurofibromas.